A Ponderação da Extensão do Estatuto de Vítima aos Familiares da Vítima de Crime, em caso de Sobrevivência = The uestioning of extending the status of victim to the relatives of the victim of crime, in case of not dying in consequence of a crime - Guia, Maria João (Revista Eletrônica de Direito Penal e Política Criminal, 2017)
In this brief reflection I intend to address the issue of the transposition of the Directive 2012/29 / EU of the European Parliament and of the Council of 25 October 2012, after its publication in the Portuguese Law Nr 130/2015, of 4 September, in particular with regard to the question of the non-recognition and consequent impossibility of granting the status of victim of crime as enshrined in sub-paragraph (ii) to the victim's relatives in the event of the victim's survival after and in result of having been a victim of crime.To this end, I will make a very brief historical review of the rights of victims in Europe, the higher accurate attention given to the issue of crime victims in the last 15 years and the recent publication of several diplomas that focus on this issue, analyzing In detail as it was introduced in the Portuguese legal system and as such did not correspond, from its genesis, to the extent of protection of victims, in the person of the family members designated in paragraph c) of no. 1 of article 67-A of the Code of Criminal Procedure, when the victim of crime does not die, but remains in a vegetative state or unable to communicate, to reflect or to decide on their circumstances.